Indonesian Proverbs Application Design by Applying Android Horspool Boyer Moore Algorithm - Andri Agus Yahya; Nelly Astuti Hasibuan; Putri Ramadhani (The IJICS (International Journal of Informatics and Computer Science), 2018)
Proverbs are words or groups of words which states a purpose or will, circumstance of someone, something, or something that express behavior, actions and things about a person indirectly, but implicitly convey a message that can be understood by both the reader and the listener. String matching is an algorithm to search for all occurrences of short and long strings, and for short strings called patterns and long strings called text. Horspool Algorithm is a simplification of the Boyer-Moore algorithm which in search of text is to search in large text to find the first pattern. Because the text sought can be very large (allowing hundreds of thousands of characters) it is important to use more efficient techniques based on that case, a search application based on android is made to make it easier for someone to find proverbs because not everyone understands this and that makes it more practical and efficient in terms of its use without having to carry proverbs in print media such as books.